Meta-Synthesis Profile of Islamic Religious Education Graduates in Indonesia - Novitasari, Dian; Thoifah, Ianatut (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
This research aims to analyze the trend of graduate profiles of Islamic religious education study programs in Indonesia and how it is relevant to the objectives of choosing an Islamic religious education study program for prospective students. This research used a qualitative approach with a meta-synthesis type of research with a meta-aggregation model. The data source was the 75 Islamic religious education study program websites throughout Indonesia. The research results show the trend of graduate profiles. Indonesia's Islamic religious education study program focuses not on religious deepening but on the social field of education. There are only 3 things in the religious field: being a da'i, hafiz, and Hajj guide. So, there is no visible relevance of the graduate profiles Islamic religious education study program with the aim of prospective students to select an Islamic religious education study program who want to deepen their knowledge of the Islamic religion or learn to recite al-Qur’an. This research provides an overview in compiling graduate profiles of Islamic religious education in Indonesia and as a reference for selecting Islamic religious education study programs for the community.